2019
DOI: 10.1088/2057-1976/aaf2c3
|View full text |Cite
|
Sign up to set email alerts
|

Viability and cell cycle studies of metastatic triple negative breast cancer cells using low voltage electrical pulses and herbal curcumin

Abstract: Cancer is a disease of cell cycle, characterized by uncontrolled cell division. The tumor suppressor gene p53 plays a major role in cell cycle control, blocking the cell progression at G 1 /S phases. In triple negative breast cancer (TNBC), the lack/mutation of p53 is a common genetic irregularity that promotes survival signals leading to tumorigenesis. Due to its unique molecular profile, aggressive behavior, and metastasis, no targeted therapies exist for TNBC. This motivates our exploration of the influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Following 4 h treatment, all cells were scraped, washed thrice with ice-cold 1 × PBS with centrifugation at 1,500 rpm at 4 °C, lysed using the RIPA buffer and sonication, as previously 69 . Lysates were cleared of debris with centrifugation at 14000 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…Following 4 h treatment, all cells were scraped, washed thrice with ice-cold 1 × PBS with centrifugation at 1,500 rpm at 4 °C, lysed using the RIPA buffer and sonication, as previously 69 . Lysates were cleared of debris with centrifugation at 14000 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…These effects were accompanied by the regulation of Bax, Bcl-2, p16, and p21 expression, which eventually led to apoptosis induction and cell cycle arrest [ 143 ]. In contrast, it has been reported that curcumin treatment decreases the expression level of p53 and phosphorylated p53 (S392, S15, S392) in MDA-MB-231, SKBR3 and EMT6 cells, representing the induction of p53- independent apoptosis in treated cells [ 108 , 144 , 145 , 146 , 147 ]. Moreover, it has been documented that Notch1 overexpression is correlated with a highly expressed mutant p53 (R280K) in MDA-MB-231 cells, in which mutant p53 acts as its transcriptional activator.…”
Section: Curcumin: Impacts On Multiple Cellular Signaling Pathways In Hormone-independent Breast Cancermentioning
confidence: 99%
“… 128 Additional studies in BC cell lines showed that ECT increased the cytotoxicity of curcumin treatment by 7-fold, 129 increased apoptosis in MDA-MB-231 cells, and minimally affected the viability of non-cancerous MCF10A cells. 129 , 130 A recent study demonstrated the anticancer effects of ECT against the MDA-MB-231 cell line, which is representative of the TNBC subtype. 131 These effects include the suppression of key proteins involved in the proliferation, differentiation, migration, survival, and apoptosis of cancer cells.…”
Section: Bcmentioning
confidence: 99%